Diagnoza organizațională (Analiza diagnostic) - Marius DODU; Sorin Dan ȘANDOR; Ciprian TRIPON (Revista Transilvană de Ştiinţe Administrative, 2004)
Organizational diagnosis is a step (some authors say the first) in a change process, having as primary goals identifying strengths and weaknesses, their causes and finding solutions intended to lead towards an improvement of the organization. The paper tries to present some of the models of organizational diagnosis that were proposed: three level model, Weisbord Six Box model, Burke-Litwin and the congruence model, discussing their advantages and disadvantages. The last part of the paper presents the requirement for a successful diagnosis, with emphasis on the specificity of the public sector.